VirusBoxing: A HIIT-based VR boxing game - Xu, W.; Liang, H.-N.; Ma, X.; Li, X. (CHI PLAY '20: Extended Abstracts of the 2020 Annual Symposium on Computer-Human Interaction in Play, 2020)
Physical activity or exercise can improve people`s health and reducetheir risk of developing several diseases; most importantly, regular activity can improve the quality of life. However, lack of time isone of the major barriers for people doing exercise. High-intensity interval training (HIIT) can reduce the time required for a healthy exercise regime but also bring similar benefits of regular exercise.We present a boxing-based VR exergame called VirusBoxing to promote physical activity for players. VirusBoxing provides players with a platform for HIIT and empowers them with additional abilities to jab a distant object without the need to aim at it precisely.In this paper, we discuss how we adapted the HIIT protocol and game play features to empower players in a VR exergame to give players an efficient, effective, and enjoyable exercise experience.